The Influence Of Bacteriocin On The Soft Liner Tensile Strength And Its Inhibitory Effect On Candida Albicans (Mustansiria Dental Journal, 2022)
Aim of the study. Many efforts were applied to use new antimicrobial agents due to the recent appearance of bacterial resistance to treatment. One of the antimicrobial agents is the Bacteriocin. Bacteriocins are small molecules produced by probiotics bacteria and have the ability to minimize pathogens colonization. This study performed to evaluate the effect of bacteriocin against candida albicans growth, inhibition of the formation of biofilm and tensile strength of the hot soft liner and compare the results with the use of denture cleanser tablets.Materials and Methods. Two types of specimens were prepared first type to measure the tensile strength for the soft liner and the other type to measure the inhibition of growth and the biofilm of C. albicans.  Each type was divided into subgroups (15 specimens each) to be immersed in water as control, Bacteriocin and denture cleansing tablets at different intervals. For the tensile strength test, rectangular hot cure soft denture liner specimens prepared with dimensions of 80mm*9mm*3mm length, width and thickness respectively. While for microbiological test, 10mm diameter and 3mm thick discs of heat cured soft lining material were prepared. The specimens used for the tensile strength test were divided into three groups according to the immersion method: 1st group is the control immersed in water, 2nd group immersed in Bacteriocin and 3rd group immersed in denture cleansing tablet (Lacalut DENT Cleaning tabs/Germany). While for the microbiological test the specimens divided into control group, group treated with bacteriocin for 1 day and group treated with bacteriocin for 15 and 30 days. The same thing done for the specimens cleaned by denture cleansing tablets. The immersion was performed by placing the specimens in tube (10ml) filled with bacteriocin or cleansing tablet in water and kept for 15min. Then the specimens were removed from the tube and cleaned with tapped water and stored in distilled water. This was repeated for 15 days for the first group, and 30 days for the other group. The tensile strength was measured by the Instron testing machine, the inhibition of C.albicans growth and biofilm formation was tested by co-cultured method.